Study of exercise-induced desaturation in chronic obstructive pulmonary disease patients visiting tertiary care center in Bangalore - G, Anjali; Deepak Kumar R,; Sivasankari R,; Puneet Komarla Nagendra, (Asian Journal of Medical Sciences, 2023)
Background: Chronic obstructive pulmonary disease (COPD) patients often have a lower ability to exercise and muscle weakness, both decreasing their quality of life. The 6 min walk test (6MWT) offers insightful data on the functional capacity of respiratory variables on exercise performance. A significant reduction in oxygen saturation (SpO2) throughout the test signifies a lower tolerance for exercise or additional oxygen requirement. Aims and Objectives: This study focuses to investigate desaturation in COPD patients with normal resting oxygen levels (normoxemic) employing the 6MWT. The objective of the study defines to analyze different clinical parameters such as smoking behavior, 6MWT, and clinical parameters of COPD patients to diagnose respiratory performance. Materials and Methods: Between June 2019 and May 2020 study was conducted on patients presenting to our OPD, who were above 40 years and diagnosed with COPD, with baseline SpO2 ≥90%. 6MWT was performed on them as per American Thoracic Society guidelines. Noting their distance covered and desaturation if present. Results: The study group included 60 patients; the group was divided into 35 desaturators (DS) and 25 Non-DS (NDS) based on fall in SpO2 during 6MWT, all current smokers were in the DS group and had low body mass index values, DS group covered less distance when compared to NDS, DS had low mean forced vital capacity and forced expiratory volume 1 second values. Conclusion: This study established the relationship between COPD risk variables and 6MWT. The 6MWT was identified as a useful method to examine respiratory performance by noting exercise-induced desaturation and in turn the respiratory capacity among COPD patients.